Differential expression of interferon-gamma and interferon-gamma-inducing cytokines in Thai patients with scrub typhus or leptospirosis. - Chierakul, W; de Fost, M; Suputtamongkol, Y; Limpaiboon, R; Dondorp, A; White, N; van der Poll, T (2004)
Interferon (IFN)-gamma plays an important role in the induction of a type 1 immune response against intracellular pathogens. We compared the plasma levels of IFN-gamma and IFN-gamma-inducing cytokines in adult Thai patients with scrub typhus, caused by the obligate intracellular bacterium Orientia tsutsugamushi, and leptospirosis, caused by extracellular Leptospira interrogans. IFN-gamma, interleukin (IL)-18, and IL-15 levels were elevated only in patients with scrub typhus, whereas IL-12p40 and tumor necrosis factor-alpha concentrations were elevated in both patient groups, although more so in scrub typhus. These data suggest a role for a cell-mediated immune response in host defense against O. tsutsugamushi.